Preparation and Performance of an Adsorption Type Gel Plugging Agent as Enhanced Oil Recovery Chemical. (13th December 2015) - Qin, Xiaoping; Zheng, Jiapeng; Li, Liangchuan; Li, Cuixia; Sun, Guiling; Lu, Haiwei; Peng, Tong
Abstract : A novel adsorption type gel plugging agent (ATGPA) was prepared using acrylamide (AM), acrylic acid (AA), diallyl dimethyl ammonium chloride (DMDAAC), 2-acrylamido-2-methylpropanesulfonate (AMPS), formaldehyde (HCHO), resorcinol (C6 H6 O2 ), and thiocarbamide (CH4 N2 S) as raw materials under mild conditions. ATGPA was characterized by infrared (IR) spectroscopy, elemental analysis, and scanning electron microscope (SEM). It was found that ATGPA exhibited higher elastic modulus (G ′ ) and viscous modulus (G ′ ′ ) than AM/AA gel plugging agent (AAGPA) under the same scanning frequency. It was also found that ATGPA had moderate temperature resistance and salt tolerance. Core plugging tests results indicated that ATGPA could achieve up to higher plugging rate (P R ) than AAGPA (97.2% versus 95.7%) at 65°C. In addition, ATGPA possessed stronger antiscouring ability by core plugging experiments at 65°C.